Time-space domain nearfield acoustical holography for visualizing normal velocity of sources. (May 2020) - Aujogue, Nicolas; Ross, Annie; Attendu, Jean-Michel
Highlights: Time-space domain formalism allows reconstruction of normal velocity of structures. This technique suppresses errors due to spectral leakage and circular deconvolution. This method outperforms methods based on frequency-wavenumber formalism. Abstract: In this paper, the time-space domain Green's function relating the sound pressure to the normal velocity of particles is used to adapt time-space domain nearfield acoustical holography (TSD-NAH) to recover the transient normal velocity of a planar source from acoustic measurements. This method provides a simple and effective visualization of the time-evolving vibration field of plate-like structures. Numerical results on a baffled membrane model show that this method avoids some of the signal processing errors introduced by other state-of-the-art methods. A case study on a baffled plate shows that the velocity reconstruction remains satisfactory (with less than 20 % error) for back-propagation distances up to 10 cm and typical signal-to-noise ratios ( ⩾ 20 dB). Finally, TSD-NAH is applied on an experimental set of data obtained from a plexiglass plate impacted with a steel rod; the computed velocity field is visualized in time and space domains. It is then showed that the computed velocity field can be used to recover unknown properties of the source. In particular, the Young's modulus of the tested plate has been estimated with a precision better than 5 % .